1963
DOI: 10.1055/s-0037-1621228
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Y91 as an Inert Indicator in Intestinal Absorption Tests

Abstract: SummaryIn this paper is reported the use of Y91 as an inert-indicator in the studies of the intestinal absorption of I131-labelled substances, emphasis being given to its clinical advantages.The Y91 is not absorbed in the gastrointestinal tract, since recovery in the faeces in 22 cases was 96 ± 6.7% (S.D.) of the amount given.The Y91 and the I131-labelled substances are homogenously distributed throughout any given stool sample but their rate of excretion is not always parallel.A close correlation was found be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…However, there were doubts about the role of ascorbic acid in those results because the comparison groups in that study received only unfortified water. The results obtained in the previous study might have been due to the sum of the increased iron and ascorbic acid ingestion, since the role of ascorbic acid as a facilitator of non-heme iron absorption is well recognized [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there were doubts about the role of ascorbic acid in those results because the comparison groups in that study received only unfortified water. The results obtained in the previous study might have been due to the sum of the increased iron and ascorbic acid ingestion, since the role of ascorbic acid as a facilitator of non-heme iron absorption is well recognized [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many studies conducted in the 1970s and 1980s had already demonstrated the possibility of improving iron nutriture by adding sources of ascorbic acid such as fruit [14], fruit juices [14,17], fortified drinks [15], and vegetables [16] to the usual diet. However, the advantage of the present study was the use of drinking water as a vehicle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation